Persistent hypercalcaemia associated with two pathogenic variants in the CYP24A1 gene and a parathyroid adenoma—a case report and review - Leszczyńska, Dorota; Szatko, Alicja; Latocha, Julia; Kochman, Magdalena; Duchnowska, Maria; Wójcicka, Anna; Misiorowski, Waldemar; Zgliczyníski, Wojciech; Glinicki, Piotr (Frontiers in Endocrinology, 2024)
Introduction 24-Hydroxylase, encoded by the CYP24A1 gene, is a crucial enzyme involved in the catabolism of vitamin D. Loss-of-function mutations in CYP24A1 result in PTH-independent hypercalcaemia with high levels of 1,25(OH)2D3. The variety of clinical manifestations depends on age, and underlying genetic predisposition mutations can lead to fatal infantile hypercalcaemia among neonates, whereas adult symptoms are usually mild. Aim of the study We report a rare case of an adult with primary hyperparathyroidism and loss-of-function mutations in the CYP24A1 gene and a review of similar cases. Case presentation We report the case of a 58-year-old woman diagnosed initially with primary hyperparathyroidism. Preoperatively, the suspected mass adjoining the upper pole of the left lobe of the thyroid gland was found via ultrasonography and confirmed by 99mTc scintigraphy and biopsy as the parathyroid gland. The patient underwent parathyroidectomy (a histopathology report revealed parathyroid adenoma), which led to normocalcaemia. After 10 months, vitamin D supplementation was introduced due to deficiency, and the calcium level remained within the reference range. Two years later, biochemical tests showed recurrence of hypercalcaemia with suppressed parathyroid hormone levels and elevated 1,25(OH)2D3 concentrations. Further investigation excluded the most common causes of PTH-independent hypercalcaemia, such as granulomatous disease, malignancy, and vitamin D intoxication. Subsequently, vitamin D metabolites were measured using LC–MS/MS, which revealed high levels of 25(OH)D3, low levels of 24,25(OH)2D3 and elevated 25(OH)2D3/24,25(OH)2D3 ratios, suggesting a defect in vitamin D catabolism. Molecular analysis of the CYP24A1 gene using the NGS technique revealed two pathogenic variants: p.(Arg396Trp) and p.(Glu143del) (rs114368325 and rs777676129, respectively). Conclusions The diagnostic process for hypercalcaemia becomes complicated when multiple causes of hypercalcaemia coexist. The measurement of vitamin D metabolites using LC–MS/MS may help to identify carriers of CYP24A1 mutations. Subsequent molecular testing may contribute to establishing the exact frequency of pathogenic variants of the CYP24A1 gene and introducing personalized treatment.